T&C Furniture / Nurina Mulhiwaty Damanhuri … [et al.] - Damanhuri, Nurina Mulhiwaty; Ibrahim, Azyra Fyazlyn; Mohd Sani, Husna; Hashim, Siti Aisha; Hamid, Siti Nor Hajar; Harun, Norazman; Omar, Roaimah; Mohd Amir Hamzah, Afzan Sahilla (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Desks and chairs are two things that we can find it almost in every house. These two things are very important in human's life likes we are completing each other. They make our life more comfort such as desk-we can use it as a medium to put something on it while chair we can seat on it comfort. Our group will invent one product by combining the desk and the chair together in one design. A desk chair is one of the most useful and helpful furniture that I would recommend to people who live in small rooms or who constantly live outside from their house. The technology of desk chair makes them handy in tight situations. People will surely appreciate the two functions of the desk chair and they can benefit from it in several ways as well. This product is invented to help and ease the people who likes to travel or for the campers. They always faced some problem whether they do not have the desk to place their things on. To make this furniture, we are using some plywood’s, carpenter's glue, nails, sandpaper and paint. There are some advantages of this invention such as unfold accommodation. If you do not have a desk or if that desk is already occupied and you still have more things to provide a place to put on, the desk chair will surely be of big help. The same chair that your guest sat on the entire day can be transformed into a desk your guest can put some things to put on it or when they want to eat. Also, one of the best advantages of the desk chair is the fact that you are buying two types of furniture for the price of one. Buying the desk and the chair separately may cost double or triple the price of the single desk chair. It saves on money the same way it saves on time and space. This is the sort of practicality a lot of people nowadays really go for.